Effect of Interest Rate on Customers’ Demand for Loans in Atiwa Rural Bank PLC, Ghana - Raymond Obeng Boateng; Albert Mensah; Daniel Osei; Abdul Wahab Atta Bashiru; Oscar Agyemang Opoku (Pusat Publikasi Nusantara, 2024)
This study sought to determine the influence of interest rate on demand for loans among Rural Banks in Ghana. The study adopts an explanatory design of the quantitative approach. Secondary data from the Atiwa Rural Bank PLC database was used. The data were analysed using frequencies and percentages. Also, binary logistic and linear regression were used in analysing the relationship among the key variables of this research. The study found that interest rate of Atiwa Rural Bank PLC was rated as moderate while repayment status was high. There were differences between the category of the respondents and the repayment status. More males repay their loans as compared to females and groups. Also, differences existed between the employment status of the respondents and the repayment status. Moreover, insignificant differences were identified between the employment status of the respondents and the repayment status. Interest rate affects loan period positively. Also, a strong positive correlation between interest rate and loan period was determined. Interest rate affects amount of facility negatively. Moreover, credit facility with high interest rate is 1.020 times more likely to default in paying back the credit facility as compared to respondents who obtained their credit facility as a moderate or low interest rate. Increasing interest rate was associated with low or default in repayment of credit facility. The study therefore, recommend that management of the Atiwa Rural Bank PLC put up measures to able to track and retrieve all small amount of facility or loans given to clients. Also, the management of the Atiwa Rural Bank PLC should target more salaried workers and loans used for emergency services such as medical bills, school fees among others in order to reduce Non-Performing Loans (NPL). Moreover, the management of the Atiwa rural bank should improve upon the mechanisms implemented regarding giving of group loans and repayment issues.